SUFFOCATING DELHI: - DELHI AIR POLLUTION, ITS CONSEQUENCE ON HUMAN HEALTH IN SPECIFICATION WITH, HINDERENCE TO RIGHT TO LIFE - Nair, Akshara A.; Satheesh, Aswathy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Over the past few years, pollution-related health concerns have affected India, a member of the UN. A recent analysis by the UNEP examined how human rights include the right to a healthy environment. As a champion and supporter of human rights, the UN launches initiatives, policies, and plans to support and uphold peace, collaboration, and human rights among its member nations. Delhi air pollution is still a matter of concern and is associated with health difficulties, respiratory ailments, and lung-related disorders among Delhiites, despite the government's efforts to mitigate the impacts of pollution and smog. Smog and particle matter have long been problems for Delhi, the capital city of the country, and Delhi NCR.